Mechanical circulatory support for the visually impaired: is it appropriate?. (March 2011) - Ravi, Yazhini; Firstenberg, Michael; Crestanello, Juan; Sai Sudhakar, Chittoor B
Long-term mechanical circulatory support devices, especially left ventricular assist devices, are being increasingly utilized in the management of end-stage heart failure either as bridge to heart transplantation, recovery or as destination therapy. However, current technology for controllers and alarm systems for left ventricular assist devices does not permit their implantation in eligible patients with visual impairment. We report two patients in whom the decrease in visual acuity was a significant factor in determining eligibility for long-term mechanical circulatory support.